KAJIAN TINGKAT PENGETAHUAN DAN KECEMASAN TERHADAP PANDEMI COVID-19 PADA MASYARAKAT PESISIR DI KECAMATAN MOYO UTARA KABUPATEN SUMBAWA - Neti Apriati; Iga Maliga; Nikodimus Margo Rinenggantyas (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Coronavirus Disease 2019 or Covid-19 is an infectious disease caused by a new virus, namely the Coronavirus, which spreads easily and causes a high mortality rate. Knowledge is everything that is known based on human experience itself and knowledge will increase according to the process of experience experienced by individuals. Knowledge is very important for all people to avoid risks such as anxiety, panic and stress during the Covid-19 pandemic. Anxiety is an emotional state that arises when individuals are experiencing stress which is characterized by a feeling of tension in the mind that makes individuals feel worried and accompanied by physical responses such as a racing heart, rising blood pressure and others. Coastal communities are people who are left behind economically, socially, especially in terms of education and health services. The purpose of this study was to determine the relationship between knowledge level and anxiety about the Covid-19 pandemic in coastal communities in Ai-Bari Hamlet, Kukin Village, North Moyo District. This study uses a descriptive correlative study design with a quantitative approach and uses Jaspen's M Correlation Test. The results show that most respondents have a good level of knowledge, 50 respondents (41.7%), while the anxiety level of the majority of respondents is at the level of not anxious 58 people ( 48.3%). The results of the jaspen's M test obtained the value of M = -0.1. The conclusion in this study shows a significant relationship between knowledge and anxiety levels with the result value using the Jaspens's M correlation test where r count > r table (0.38 > 0.21) then the hypothesis H0 is rejected, and H1 is accepted.